Effects of inoculants on the fermentation characteristics and in vitro digestibility of reed canary grass (Phalaris arundinacea L.) silage on the Qinghai‐Tibetan Plateau. (23rd March 2020) - Chen, Liangyin; Li, Ping; Gou, Wenlong; You, Minghong; Cheng, Qiming; Bai, Shiqie; Cai, Yimin
Abstract: To effectively use local available grass resources to cover the winter feed shortage on the Qinghai‐Tibetan Plateau, direct‐cut and wilted reed canary grass (RCG) silages were prepared by using a rolled‐bale system, and their ensiling characteristics and in vitro digestibility were studied. Silages were treated without (control) or with inoculants including LP ( Lactobacillus plantarum ), LPLB ( L. plantarum, L. buchneri ), and LPLBc ( L. plantarum, L. buchneri, and cellulase), and were stored at ambient temperature (5.7–14.6°C) for 90 days. Compared with control, the inoculated silages increased ( p  < .05) lactic acid and acetic acid contents, and reduced ( p  < .05) final pH value and ammonia‐N ratio of total N. The highest WSC content (41.2 g/kg DM) occurred for LPLB‐inoculated silage, whereas LPLBc‐treated silage displayed the lowest contents of NDF (522.9 g/kg DM) and ADF (275.5 g/kg DM). In addition, LPLBc‐inoculated silage had the highest in vitro gas production (51.0 ml/g DM), in vitro DM digestibility (619.3 g/kg DM), and metabolic energy (9.6 kJ/kg DM). These results confirmed that treatments with inoculants at ensiling could improve silage fermentation and in vitro digestibility of RCG, and this could be a potential winter feed for animals on the Qinghai‐Tibetan Plateau.